Electrical characterization of GaN-based layer structures - Firdous Banu (2011)
Wide band gap semiconductors are attractive for several microelectronic and photonic applications such as high power amplifiers, LEDs and laser diodes. Particularly, GaN-based semiconductors are promising as they exhibit attractive properties such as low intrinsic carrier concentration and high thermal conductivity, even at high operating temperatures and harsh environments. In this project, GaN-based wide bandgap semiconductor materials grown using molecular beam epitaxy were studied. Electrical characterization including Current-voltage and Capacitance-voltage characteristics were carried out and the results were analyzed and correlated with growth parameters. Carrier profile measurements were also performed and studied. Temperature dependent test such as the low temperature Hall Effect measurement was also done on the MBE grown wafers to measure the electrical characterization. I also learnt simple microfabrication steps to produce semiconductor devices and analyze their performance.